2014
DOI: 10.1111/jdv.12869
|View full text |Cite
|
Sign up to set email alerts
|

TH17 cells, interleukin‐17 and interferon‐ γ in patients and households contacts of leprosy with multibacillary and paucibacillary forms before and after the start of chemotherapy treatment

Abstract: The principal finding was that TH17 lymphocytes and interleukin-17 actively participating in the immune response of Hansen's disease as well these cells can stimulate the cellular immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Our result agrees with Nada and Saini [21,22]. Also INF-γ was higher in PB than in MB which is concordant with the results of De Almeida-Neto, Nada, Saini, and Madan [21,23,30]. The pauci bacillary (PB) types of infection are portrayed by the power of a Th1-type immune response, the nearness of all around shaped granulomas at the site of the injury because of fiery CMI, and control of mycobacterial replication.…”
Section: Discussionsupporting
confidence: 93%
“…Our result agrees with Nada and Saini [21,22]. Also INF-γ was higher in PB than in MB which is concordant with the results of De Almeida-Neto, Nada, Saini, and Madan [21,23,30]. The pauci bacillary (PB) types of infection are portrayed by the power of a Th1-type immune response, the nearness of all around shaped granulomas at the site of the injury because of fiery CMI, and control of mycobacterial replication.…”
Section: Discussionsupporting
confidence: 93%
“…A recent study explored the relationship between pancreatic cancer, S100A9/A8 and transforming growth factor beta 1 (TGFβ1) concluded that the overexpression of S100A9/A8 by infiltrating inflammatory cells and the expressions is related to TGFβ1 in pancreatic ductal adenocarcinoma (PDAC) . Interleukin‐17 (IL‐17), a pro‐inflammatory cytokine mainly produced by T‐helper 17 (Th 17) cells, has been reported to play a crucial role in the development of an effective immune response . Liu et al reported that IL‐17 played a pivotal role in the pathogenesis of numerous inflammatory diseases in the central nervous system (CNS), such as multiple sclerosis and stoke, whereas Dai et al suggested that serum IL‐17 was an early prognostic biomarker of severe acute pancreatitis in patients receiving continuous blood purification .…”
Section: Introductionmentioning
confidence: 99%
“…11 Interleukin-17 (IL-17), a pro-inflammatory cytokine mainly produced by T-helper 17 (Th 17) cells, has been reported to play a crucial role in the development of an effective immune response. 12,13 Liu et al reported that IL-17 played a pivotal role in the pathogenesis of numerous inflammatory diseases in the central nervous system (CNS), such as multiple sclerosis and stoke, 14 whereas Dai et al suggested that serum IL-17 was an early prognostic biomarker of severe acute pancreatitis in patients receiving continuous blood purification. 15 However, few studies have appeared to place an emphasis on the effects of S100A9 and the release of proinflammatory cytokines through the IL-17 signalling pathway in AP.…”
mentioning
confidence: 99%
“…Interleukin 17A (IL-17A) is generally considered as a proinflammatory cytokine. IL-17A has been shown to play a protective role in the early stages of infection by triggering macrophages and boosting Th1 effector cells (6,7). Saini et al discovered CD4 + Th17 cells in the patients infected with Mycobacterium tuberculosis and emphasized the significance of these cells in leprosy.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin 17A (IL-17A) is generally considered as a pro-inflammatory cytokine. IL-17A has been shown to play a protective role in the early stages of infection by triggering macrophages and boosting Th1 effector cells ( 6 , 7 ). Saini et al.…”
Section: Introductionmentioning
confidence: 99%